ANTHROPOMETRIC INDICES FOR ESTIMATING OVERWEIGHT AND OBESITY IN SCHOOL-AGED CHILDREN FROM NORTH MACEDONIA - Zafirova, Biljana; Chadikovska, Elizabeta; Trpkovska, Biljana; Stojanoska, Biljana Bojadzieva (Journal of Morphological Sciences, 2021)
Anthropometrics are a set of non-invasive, quantitative body measurements used to assess growth, development and health parameters. Waist circumference (WC) and waist -to-hip ratio (WHR) are the measurements most commonly used to estimate abdominal obesity while BMI used to determine general obesity. Our goal in this study was to find cut-off points of selected anthropometric indices for estimating overweight and obesity in school-aged children aged 6 to 8 years from North Macedonia. In this study, a total of 603 children (300 boys and 303 girls) were investigated. Anthropometric indicators were measured using a standard protocol. We selected four parameters to measure (weight, height,) and two circumferences (waist WC and hip HC). The following indices were taken into consideration: Body mass index (BMI), WC and waist-to-hip-ratio (WHR). Percentile distribution of the tested variables was done by age and sex.Some of anthropometric parameters have shown significant age- and sex-specific differences in favour of boys, with exception of WHR. The prevalence of overweight and obesity across BMI cut-off points was 16% in boys and 15, 1% in girls. Girls had the prevalence of abdominal obesity of 12 % WC and WHR 13,2%. Both cut-off points for the boys were 11% WC and 10% WHR. However, the Macedonian cut-off points for WC and WHR showed a slightly elevated prevalence of abdominal obesity among girls.These results and determination of BMI, WC, WHR cut-off values can be used for estimating overweight and obesity and consequences associated with it in school-aged children aged 6 to 8 years from North Macedonia. Kew words : BMI, WC, WHR, school-age children, anthropometry https://doi.org/10.55302/JMS2142147z